Brief training in mindfulness meditation reduces symptoms in patients with a chronic or recurrent lifetime history of depression: A randomized controlled study. (December 2017) - Winnebeck, Emilia; Fissler, Maria; Gärtner, Matti; Chadwick, Paul; Barnhofer, Thorsten
Abstract: Background: Training in mindfulness has been introduced to the treatment of depression as a means of relapse prevention. However, given its buffering effects on maladaptive responses to negative mood, mindfulness training would be expected to be particularly helpful in those who are currently suffering from symptoms. This study investigated whether a brief and targeted mindfulness-based intervention can reduce symptoms in acutely depressed patients. Methods: Seventy-four patients with a chronic or recurrent lifetime history were randomly allocated to receive either a brief mindfulness-based intervention (MBI) encompassing three individual sessions and regular home practice or a control condition that combined psycho-educational components and regular rest periods using the same format as the MBI. Self-reported severity of symptoms, mindfulness in every day life, ruminative tendencies and cognitive reactivity were assessed before and after intervention. Results: Treatment completers in the MBI condition showed pronounced and significantly stronger reductions in symptoms than those in the control condition. In the MBI group only, patients showed significant increases in mindfulness, and significant reductions in ruminative tendencies and cognitive reactivity. Conclusions: Brief targeted mindfulness interventions can help to reduce symptoms and buffer maladaptive responses to negative mood in acutely depressed patients with chronic or recurrent lifetime history. Highlights: We compared brief mindfulness training against resting control in acutely depressed patients. Patients in the mindfulness condition showed stronger reductions in symptoms. The results support the use of mindfulness in the treatment of acute depression.